Are Street Vendors Really Innovative Toward Self-service Technology?. Issue 2 (2nd April 2016) - Kaushik, Arun Kumar; Rahman, Zillur
Abstract : Street vending has acquired great importance in present times. This study attempts to link consumer innovativeness (CI) to street vending – an ancient occupation now emerging as a new market form using technology and innovation. The study investigates the behavior of street vendors (a group hypothesized to enjoy more innovativeness than those with similar socioeconomic backgrounds) regarding adoption of self-service technologies (SSTs) in the retail banking industry. In addition to primary research instruments, in-depth interviews were conducted with representatives of the two groups under study (street vendors and formal wage workers) to determine their awareness levels, usage, primary sources of information and reasons behind the adoption of the three SSTs considered along with their dependence on opinion leaders for making adoption decisions. Findings reveal that compared to formal wage workers, street vendors exhibit lower levels of innovativeness toward SSTs, and consumers are driven by three prime correlates of age, gender and income. Further, informal groups of street vendors earn higher income despite being less qualified technically or otherwise than the formal sector wage earners within their social class. These results will help practitioners revisit their existing marketing strategies and policies to increase the reach of self-service technology among urban lower middle class in India.